Physiological and biochemical attributes of the association host-parasite Tamarix aphylla-Plicosepalus acacia - Barhoumi, Zouhaier (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.